Analisis Infrastruktur Teknologi Informasi pada Sistem Pengiriman Paket di Lion Parcel Palembang - Rosita Azaly; Vany Alia Putri; Agung Prayoga; Fenny Purwani (PT Jurnal Cendekia Indonesia, 2026)
This study aims to analyze the Information Technology Infrastructure that supports the package delivery system at Lion Parcel Palembang. Information technology infrastructure plays an important role in ensuring the effectiveness, efficiency, and continuity of logistics service operations. The research employed a qualitative descriptive approach through observation and interviews with operational staff involved in package delivery activities. The analysis focused on seven components of Information Technology Infrastructure, namely hardware, software, network, data and database, human resources, security, and IT services. The results indicate that Lion Parcel has implemented an integrated information system that supports package delivery processes, including customer data management, shipment tracking, transaction recording, and real-time delivery status updates. The implementation of information technology has improved operational efficiency, accelerated customer service, and reduced manual recording errors. However, several issues were identified, including system downtime during updates, server disruptions caused by new feature implementation, and dependence on centralized systems managed by the head office. Therefore, improvements such as server capacity optimization, backup and recovery implementation, enhanced system security, and continuous infrastructure monitoring are recommended. Overall, the existing information technology infrastructure has adequately supported operational activities but still requires further optimization to improve service reliability and performance.